-7(5x+-6)=-3(-9x-11)+9

Simple and best practice solution for -7(5x+-6)=-3(-9x-11)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(5x+-6)=-3(-9x-11)+9 equation:


Simplifying
-7(5x + -6) = -3(-9x + -11) + 9

Reorder the terms:
-7(-6 + 5x) = -3(-9x + -11) + 9
(-6 * -7 + 5x * -7) = -3(-9x + -11) + 9
(42 + -35x) = -3(-9x + -11) + 9

Reorder the terms:
42 + -35x = -3(-11 + -9x) + 9
42 + -35x = (-11 * -3 + -9x * -3) + 9
42 + -35x = (33 + 27x) + 9

Reorder the terms:
42 + -35x = 33 + 9 + 27x

Combine like terms: 33 + 9 = 42
42 + -35x = 42 + 27x

Add '-42' to each side of the equation.
42 + -42 + -35x = 42 + -42 + 27x

Combine like terms: 42 + -42 = 0
0 + -35x = 42 + -42 + 27x
-35x = 42 + -42 + 27x

Combine like terms: 42 + -42 = 0
-35x = 0 + 27x
-35x = 27x

Solving
-35x = 27x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27x' to each side of the equation.
-35x + -27x = 27x + -27x

Combine like terms: -35x + -27x = -62x
-62x = 27x + -27x

Combine like terms: 27x + -27x = 0
-62x = 0

Divide each side by '-62'.
x = 0

Simplifying
x = 0

See similar equations:

| 4(x+1)=2(x-3)-1(1-2x) | | -25+7+11=35 | | -42+s=-46 | | A=-25 | | 7x-6(x+4)=-114 | | 4m+14-2m= | | -3.5y=-50 | | 7x+24=2x-6 | | 4.5-2.6+x=9 | | -9b+13-12=10 | | 75n=30 | | -4(x-2)=-40 | | 25+4-6=12 | | 3x-40=6x-10 | | 46-12+6=12 | | 4+3-5=7 | | 3+4(X+4)=27 | | 9x^2+36x+14=0 | | R+(-1.5)=-3.4 | | 18u(8)w(8)+30u(6)w(5)y(4)= | | 11x-2=x | | -15+8-14=35 | | 4-3+5=7 | | 3(7x-7)+13x= | | 4500+(4*x)+600=10,500 | | 11-(3x-6)+2(2x+5)-x= | | 4x+14-6=7 | | 45+16-2=14 | | (3*1500)+(4*x)+(3*200)=10,500 | | 0.4m-3= -1 | | 3x-5(x-5)=-6+3+21 | | 6+12+3=39 |

Equations solver categories